Differential Response to an Algae Supplement High in DHA Mediated by Maternal Periconceptional Diet: Intergenerational Effects of n‐6 Fatty Acids. Issue 8 (5th July 2014) - Clayton, Edward H.; Lamb, Tracy A.; Refshauge, Gordon; Kerr, Matthew J.; Bailes, Kristy L.; Ponnampalam, Eric N.; Friend, Michael A.; Hopkins, David L.
Abstract: Algae high in docosahexaenoic acid (DHA) may provide a source of long‐chain omega‐3 polyunsaturated fatty acids (LCn‐3PUFA) for inclusion in the diet of lambs to improve the LCn‐3PUFA status of meat. The effect of background LCn‐3PUFA status on the metabolism of high DHA algae is, however, unknown. The aim of the current study was to determine whether the response to a high in DHA algae supplement fed to lambs for six weeks prior to slaughter was mediated by a maternal periconceptional diet. Forty Poll Dorset × Border Leicester × Merino weaner lambs were allocated to receive either a ration based on oat grain, lupin grain, and chopped lucerne (control) or the control ration with DHA‐Gold™ algae included at 1.92 % DM (Algae) based on whether the dams of lambs had previously been fed a diet high in n‐3 or n‐6 around conception. LCn‐3PUFA concentration was determined in plasma and red blood cells (RBC) prior to and following feeding. The concentrations of EPA and DHA in the plasma and RBC of lambs receiving the control ration were significantly ( p < 0.001) lower when lambs received the ration for 14 days compared with pre‐feeding concentrations. The concentrations of EPA and DHA were also significantly ( p < 0.001) higher when lambs consumed the Algae ration compared with the control ration for 42 days. The increase in EPA and DHA was, however, significantly ( p < 0.05) lower if lamb dams had previously been fed a diet high in n‐6 at conception. Assessing the previous nutrition and n‐3 status of lambs may allow producers to more accurately predict the likely response to supplements high in LCn‐3PUFA, particularly, DHA.